2016
DOI: 10.1002/2016jd025463
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the interdecadal variability of summer precipitation in central Japan using a reconstructed 106 year long oxygen isotope record from tree ring cellulose

Abstract: We present a unique proxy for reconstructing the interannual variability of summer precipitation associated with the quasi‐stationary front (Baiu front) in central Japan. The rainfall from the Baiu front has a relatively lower oxygen isotopic composition than other types of nonfrontal precipitation. The variability in the oxygen isotopes in summer rainfall is closely related to the Baiu frontal activity. In this study we used a mechanistic tree ring isotope model to reconstruct a 106 year long oxygen isotopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 86 publications
0
8
0
1
Order By: Relevance
“…The tree-ring cellulose oxygen isotope model used for this study is based on the model reported by Kurita et al [8], as modified from Roden et al [7]. It is a mechanistic model used to quantify both physical and biochemical fractionation associated with treering cellulose δ 18 O, including the uptake of soil water (source water), transpiration and photosynthesis in leaves, and cellulose synthesis.…”
Section: Proxy System Model Of Tree-ring Cellulose Oxygen Isotopic Comentioning
confidence: 99%
See 3 more Smart Citations
“…The tree-ring cellulose oxygen isotope model used for this study is based on the model reported by Kurita et al [8], as modified from Roden et al [7]. It is a mechanistic model used to quantify both physical and biochemical fractionation associated with treering cellulose δ 18 O, including the uptake of soil water (source water), transpiration and photosynthesis in leaves, and cellulose synthesis.…”
Section: Proxy System Model Of Tree-ring Cellulose Oxygen Isotopic Comentioning
confidence: 99%
“…The model was applied to the transpiration of leaf water [13]. Leaf water δ 18 O is given as [8,14] =…”
Section: Proxy System Model Of Tree-ring Cellulose Oxygen Isotopic Comentioning
confidence: 99%
See 2 more Smart Citations
“…) 。また,年輪における酸素同位体比が 相対湿度や降水量との相関が高いことから,降水 や水循環の指標として期待されている (Kurita et al, 2016;Sakashita et al, 2017) 。一方で,農 業の生産性に大きく関与する夏期の気温の復元に ついてはまだ知見が少ない (Davi et al, 2002) 。 これまで温帯から亜寒帯にかけて,針葉樹の年 輪内最大密度が夏期の気温を反映する指標とし て用いられている (Parker and Henoch, 1971;Schweingruber et al, 1978;Yasue et al, 1998 (Cook et al, 2013) . adj :自由度調整済み決定係数, **,*:p < 0.01 および 0.05 で有意.正の RE,CE は推定値と実測値の一致性が偶然による変動より大きいことを示す. The entire period of meteorological data was divided into early half (1898⊖1949) and late half (1950⊖2001) .…”
unclassified